Analisis Hidrograf Banjir Akibat Pemindahan Alur Sungai pada Sungai Kaliyasa Baru Menggunakan Model Hec-HMS - Ratih Nurmala Saridewi; Muchamad Arif Budiyanto; Jesinta Kotilda Dinda (Universitas Batanghari Jambi, 2026)
River channel realignment is a common river engineering measure to support regional development and flood mitigation; however, it may significantly alter river hydrological characteristics. This study aims to analyze changes in flood hydrographs resulting from the realignment of the New Kaliyasa River in the PLTU Cilacap area using the HEC-HMS hydrological model. Areal rainfall was determined using the Thiessen polygon method based on annual maximum daily rainfall data from nearby rainfall stations. Design rainfall was estimated through frequency analysis using several probability distributions, namely Normal, Log-Normal, Gumbel, and Log Pearson Type III, which were evaluated using the Chi-square and Smirnov–Kolmogorov goodness-of-fit tests. The results indicate that all tested distributions are acceptable; however, the Gumbel distribution was selected as the best-fit distribution due to its smallest maximum deviation value. The selected design rainfall was then transformed into hourly rainfall using the Alternating Block Method (ABM). Hydrological modeling with HEC-HMS was conducted to generate design flood hydrographs for various return periods. The simulation results show variations in peak discharge, time to peak, and runoff volume, reflecting the hydrological response of the Kaliyasa watershed after river channel realignment. This study demonstrates that HEC-HMS is effective in representing flood characteristics and can serve as a technical basis for evaluating river capacity and planning flood control measures in the PLTU Cilacap area.